2020
DOI: 10.7150/ijms.46477
|View full text |Cite
|
Sign up to set email alerts
|

Association between Prediabetes and Renal Dysfunction from a Community-based Prospective Study

Abstract: Objective: Our study aimed to evaluate the association between prediabetes and renal dysfunction, and further assess which of glycemic indices of fasting plasma glucose (FPG), postprandial plasma glucose (PPG) and hemoglobin A1c (HbA1c) has a higher risk of renal dysfunction. Methods: This was a community-based prospective cohort study, which included 7015 participants from Beijing and Taian between May and October in 2015. The outcome was the renal dysfunction defined as est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The results suggested that the HR of incident pre-diabetes was lowest when the eGFR was around 130ml/min/1.73m 2 . Multiple studies have confirmed that pre-diabetes is strongly associated with decreased eGFR and the risk of CKD ( 15 , 17 , 38 , 39 ). It has also been shown that a decrease in eGFR is associated with an increase in IR ( 46 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results suggested that the HR of incident pre-diabetes was lowest when the eGFR was around 130ml/min/1.73m 2 . Multiple studies have confirmed that pre-diabetes is strongly associated with decreased eGFR and the risk of CKD ( 15 , 17 , 38 , 39 ). It has also been shown that a decrease in eGFR is associated with an increase in IR ( 46 ).…”
Section: Discussionmentioning
confidence: 96%
“…In general, pre-diabetes is associated with microalbuminuria, impaired kidney function, and chronic kidney disease, according to a German study (38). According to another Chinese cohort study, pre-diabetes is positively associated with renal dysfunction (OR=1.72, 95% CI 1.11-22.38) (39). By Cox proportional hazards regression model analysis, our study found that the decline in eGFR was strongly associated with an increased risk of pre-diabetes, which was consistent with The non-linear relationship between eGFR and the risk of prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[33,34] Both fasting glucose and HbA1C could be used as predictors of reduced renal function, [33,35] and postprandial glucose had a higher predictive value for renal dysfunction. [34] Moreover, high-density lipoprotein cholesterol (HDL-c) and alanine aminotransferase (ALT) are also strongly associated with prediabetes. A 5-year cohort study in a Chinese adult population revealed that the triglyceride (TG)/HDL-c ratio was positively associated with the incidence of diabetes in prediabetic patients, which was supported by the results of a 10-year follow-up study in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that prediabetes has an independent role in the development of glomerular hyperfiltration and albumin, [31,32] while prediabetes and the risk of renal dysfunction showed a positive correlation. [33,34] Both fasting glucose and HbA1C could be used as predictors of reduced renal function, [33,35] and postprandial glucose had a higher predictive value for renal dysfunction. [34] Moreover, high-density lipoprotein cholesterol (HDL-c) and alanine aminotransferase (ALT) are also strongly associated with prediabetes.…”
Section: Research Trends In Prediabetesmentioning
confidence: 99%
“…One study found that prediabetes is associated with an increased risk of neuropathy ( Kirthi et al, 2021 ). Moreover, prediabetes has been positively associated with the risk of renal dysfunction and an increased likelihood of developing kidney disease ( Echouffo–Tcheugui et al, 2016 ; Chen et al, 2020 ). Furthermore, elevated blood glucose levels have the potential to harm blood vessels within the eyes, leading to visual impairments and vision-related issues ( Priyadarshi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%